Blow-up phenomena and local well-posedness for a generalized Camassa–Holm equation in the critical Besov space. (November 2015) - Tu, Xi; Yin, Zhaoyang
Abstract: In this paper we mainly study the Cauchy problem for a generalized Camassa–Holm equation in a critical Besov space. First, by using the Littlewood–Paley decomposition, transport equations theory, logarithmic interpolation inequalities and Osgood's lemma, we establish the local well-posedness for the Cauchy problem of the equation in the critical Besov space B 2, 1 1 2 . Then we give a new blow-up criterion for the Cauchy problem of the equation. Finally, we present a new blow-up result and the exact blow-up rate of strong solutions to the equation by making use of the conservation law and the obtained blow-up criterion.